Studi On Person Over Board dalam Pendidikan dan Pelatihan Maritim di Polimarin Semarang - P. Tony Kusumartono; Hero Budi Santoso; Noviarianto Noviarianto (Jurnal Maritim Polimarin, 2020)
Person Over Board (POB) is one of the emergencies that still occurs on board, a passenger or crew member falls into the sea. This situation is very dangerous if it occurs in the middle of the ocean or in cold waters because of hypothermia which can cause unconsciousness and death within minutes. This research focuses on investigating the improvement of the response of polytechnic students during emergencies, namely Person over board (POB) with the support of manouver onboard training in Bridge Simulator as well as making decisions on safe maneuvering and precise ship response manouvre in POB rescue actions. This study uses descriptive methods to assess ship manouvre training especially when person over board (POB) among Indonesian maritime polytechnic students, which are designed for students and researchers to gather information about the conditions needed in the field of nautical studies. The rescue attempts of the Anderson, Williamson and Scharnow model of rescue turn are carried out in radar and arpa simulators, student responses with the support of manual maneuvers on board and vessel motion data which include time, distance, speed and direction of the ship or angle of target bearing. The accuracy of student responses made during a POB emergency does not always comply with the instructions in the Manouvre on Board manual. Errors occur at the beginning of the maneuver which could mean a negative impact that endangers POB safety. Safe and precise ship maneuverability in the POB situation is influenced by the time factor of the incident and when the POB is known.